2021
DOI: 10.3390/molecules26041074
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Green Solvent Performance on O,S,N-Heterocycles Synthesis: Metal-Free Click Chemistry and Buchwald—Hartwig Coupling

Abstract: The development of new and greener approaches to organic synthesis has been a trend in recent years. Continuing the latest publications of our team, in this work, we demonstrate the efficiency of three solvents: eucalyptol (1,8-cineole), cyclopentyl methyl ether (CPME), and 2-methyltetrahydrofuran (2-MeTHF) for the synthesis of O,S,N-heterocyclic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As a specific example, Campos et al 133 showed in their work the potential of solvents 79–81 to efficiently replace petroleum solvents for the synthesis of O,S,N-heterocyclic compounds. Furthermore, they included eucalyptol (1,8-cineol) (81) (Fig.…”
Section: Safer Solvents and Other Auxiliariesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a specific example, Campos et al 133 showed in their work the potential of solvents 79–81 to efficiently replace petroleum solvents for the synthesis of O,S,N-heterocyclic compounds. Furthermore, they included eucalyptol (1,8-cineol) (81) (Fig.…”
Section: Safer Solvents and Other Auxiliariesmentioning
confidence: 99%
“…The natural origin of the vegetable oils is evident, but to form a connection to CPME, it is necessary to take a look at the building blocks of the solvent, which is formed from furfural, and furfural is derived from pentoses such as xylose, and thus are regenerative raw materials, confirming its seminatural origin. 133 Therefore, a greener approach regarding natural solvents seems feasible at least for some reactions but not yet used in an industrial setting to the best of our knowledge. 132…”
Section: Alternatives To Highly Toxic Class I and Ii Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these drawbacks, we envisioned the use Raman spectrometry to live-monitor the reaction outcome in the sealed tube. As part of our recent work on the search for sustainable chemistry methods, [29][30][31] the use of some green solvents was also investigated, the results of which are presented here.…”
Section: Psp Synthesismentioning
confidence: 99%